2021
DOI: 10.12957/childphilo.2021.60940
|View full text |Cite
|
Sign up to set email alerts
|

children’s experiences of online philosophical dialogues

Abstract: Researchers are increasingly interested in the impact of philosophical dialogues with children. Studies have shown that this approach helps realise dialogic ideals in learning environments and that Philosophy with Children significantly impacts children’s cognitive and social skills. However, other aspects of this approach have attracted less attention – for example, given the focus on children’s thinking, voices and perspectives in Philosophy with Children, surprisingly few studies have examined how children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…This is a surprisingly understudied topic in both When we first decided to focus on children's perspectives, we were surprised to find how little the topic had been examined, especially given that for most people working in the field of Philosophy with Children, children's perspectives constitute a key element. Therefore, we designed a study of online philosophical dialogues during the COVID-19 lockdown and surveyed children regarding their experiences (Schaffalitzky, Jensen & Schou-Juul 2021). The survey answers indicated that the children generally enjoyed the dialogues and saw them as meaningful activities (Figure 1).…”
Section: Research Results and Other Outcomesmentioning
confidence: 99%
“…This is a surprisingly understudied topic in both When we first decided to focus on children's perspectives, we were surprised to find how little the topic had been examined, especially given that for most people working in the field of Philosophy with Children, children's perspectives constitute a key element. Therefore, we designed a study of online philosophical dialogues during the COVID-19 lockdown and surveyed children regarding their experiences (Schaffalitzky, Jensen & Schou-Juul 2021). The survey answers indicated that the children generally enjoyed the dialogues and saw them as meaningful activities (Figure 1).…”
Section: Research Results and Other Outcomesmentioning
confidence: 99%